Use of coconut shell from agriculture waste as fine aggregate in asphaltic concrete - Putra Jaya, Ramadhansyah (2015)
This study was carried out to evaluate the performance of coconut shell as fine aggregate in asphaltic concrete. The mix design incorporating penetration grade 80/100 bitumen was used to produce the specimens testing. Four coconut shell replacement levels were considered in the study: 10%, 20%, 30%, and 40%, respectively. The aggregate properties were evaluated through aggregate impact value, specific gravity and water absorption test. In addition, the performance of coconut shell in asphalt mixes was identified by volumetric properties, indirect tensile strength, resilient modulus and dynamic creep test. The results revealed that controlled specimen’s shows better volumetric properties compared to coconut shell mixes. However, 10% replacement of coconut shell indicated better performance than controlled specimen. It can be concluded that coconut shell inhibits great potential as road construction material but be only suitable for low traffic volume and at rural area.